Rapid weight loss practice and perceived problems during reduction periods of Turkish young combat athletes - Kurt, C.; Sagiroglu, I. (Journal of Physical Education and Sport, 2015)
The aim of the present study was to examine rapid weight loss practice and perceived problems during reduction periods of Turkish young combat athletes. A questionnaire which designed by researcher was used to data collection. One hundred- twelve questionnaires (62 male and 50 female were taken to statistical evaluation from the following sport: judo, karate, muay-tahi, taekwondo and wrestling. National team membership and former membership ratio to the national team were 54.5 % and 27.7 % respectively. The respondents had an average age of 21.54 ± 3.78 years, a mean body weight of 66.38 ± 11.45 kg and a mean height 170.05 ± 8.80 cm. The mean years of the sports experince was 10.42 ± 3.98 years. The mean age of start to use rapid weight loss methods were 15.29 ± 2.56 years. The primary source of information on promoting weight loss were friends (44.6 ), own method (42.90 % ), my coaches (39.30 % ) and a former combat athlete (26.80 %). The most usage methods to rapid weight loss were; more clothes on training (75 %), skipping meal (64.30%), hungry or fasting (63.4%), and saunas (58 % ). The most percieved problems during reduction period were (are); excessive fatigue (70.50 %), decrease of the physical performance (67.90 % ) and nervousness (66.10 %). On the other hand, reported binge eating episodes ratio was 60.71 %. In conclusion, despite all the warnings of the health authorities a large number of combat athletes persisted in constantly undergoing RWL methods. Therefore, International or Turkish sports federations and legislators should consider dissuasive penalties and effective education programs.